Mathematics Teachers’ Perception on Modular Distance Learning: A Phenomenological Study - Friolo, Renato V.; Mutya, Romel C. (Future Science / FSH-PH Publications, 2022)
This study aimed to capture the lived experiences of Mathematics teachers on modular distance learning. It explored mathematics teachers' perception of modular distance learning, describe the challenges, and struggles in the new normal, unveil the coping mechanisms of mathematics teachers on the demand of modular distance learning, and verify the effects of modular distance learning on students' mathematics performance. This phenomenological study used Colaizzi’s method of data analysis to interpret and analyze the data. Nine (9) teacher-participants were recruited using purposive sampling technique. The study used the interview method in gathering data. In this study, teacher-participants perceived that modular distance learning is one of the best ways to continue students' learning. However, students' mathematics performance using modular distance learning is far below the expected standard. Identified contributing factors were students' attitudes, teachers' workloads, digital infrastructure and gadgets, slow internet connections, lack of parents' support, and students' motivation. The findings of this study can be used as a basis or springboard for revision of implementing guidelines of modular distance learning enactment policies that would provide intervention to the existing identified problem.